Importance of explanation before and after forensic autopsy to the bereaved family: lessons from a questionnaire study - Ito, Takako (Journal of medical ethics, 2010)
To investigate how bereaved families felt about the explanation received before and after forensic autopsies, the authors conducted a cross-sectional survey of the bereaved families whose next of kin underwent a forensic autopsy at the two Departments of Forensic Medicine and a few bereaved families of crime victims. Of 403 questionnaires sent, 126 families responded. Among 81.5% of the respondents who received an explanation from policemen before the autopsy, 78.8% felt that the quality of the explanation was poor or improper. In Japan, the law has restricted disclosure of information from a forensic autopsy. Despite legal restrictions, 82% wanted to hear from the person who conducted the autopsy. However, police explained the results of autopsy to 65.2% of respondents. Among the families whose frustration and anger increased after autopsy, 86.4% had not been satisfied with the explanation before the autopsy. Additionally, 57.7% had not been informed on the autopsy findings at the time of the questionnaire when more than 2 years had passed after the autopsy. These results reminded us of the importance of an explanation before and shortly after a forensic autopsy for a better understanding and acceptance by bereaved families.